Changes to horizontal force-velocity and impulse measures during sprint running acceleration with thigh and shank wearable resistance. Issue 13 (3rd July 2021) - Feser, Erin H.; Bezodis, Neil E.; Neville, Jono; Macadam, Paul; Uthoff, Aaron M.; Nagahara, Ryu; Tinwala, Farhan; Clark, Kenneth; Cronin, John B.
ABSTRACT: This study determined the effects of two wearable resistance (WR) placements (i.e. thigh and shank) on horizontal force-velocity and impulse measures during sprint running acceleration. Eleven male athletes performed 50 m sprints either unloaded or with WR of 2% body mass attached to the thigh or shank. In-ground force platforms were used to measure ground reaction forces and determine dependent variables of interest. The main findings were: 1) increases in sprint times and reductions in maximum velocity were trivial to small when using thigh WR (0.00–1.93%) and small to moderate with shank WR (1.56–3.33%); 2) athletes maintained or significantly increased horizontal force-velocity mechanical variables with WR (effect size = 0.32–1.23), except for theoretical maximal velocity with thigh WR, and peak power, theoretical maximal velocity and maximal ratio of force with shank WR; 3) greater increases to braking and vertical impulses were observed with shank WR (2.72–26.3% compared to unloaded) than with thigh WR (2.17–12.1% compared to unloaded) when considering the entire acceleration phase; and, 4) no clear trends were observed in many of the individual responses. These findings highlight the velocity-specific nature of this resistance training method and provide insight into what mechanical components are overloaded by lower-limb WR.